Non-native English-speaking teachers in Korean English classrooms: reflections through critical performative pedagogy. Issue 1 (2nd January 2020) - Ahn, Soojin
ABSTRACT: This study explores non-native English-speaking teachers (NNESTs) and their critical awareness in the enacted classroom of South Korea. As a conceptual framework of this study, critical performative pedagogy (CPP) was applied to foster participants' critical reflection, and issues pertaining to the larger social discourse were discussed. Specifically, a group of four pre-service Korean English teachers participated in a semester-long CPP process that included reflection on previous learning and teaching experiences through storytelling, performances of forum theatre, critical discourse analysis (CDA) of performances, and post-discussions. The transcripts of the forum theatres were analyzed using a CDA, and the participants' written and spoken data from all activities in the CPP process were analyzed using a thematic analysis. The findings show that native speakerism is fostered in normative classroom discourse, which tends to produce marginalized learners and deficit NNEST identities. The analysis also revealed that participants can challenge the existing discourse by applying the concept of World English and the reconceptualized English teacher model. Implications of this study include the use of CPP as a mediational tool in the critical and collaborative language teacher professional development, with the potential for transformation in their real-life situations.